Development of a Computerized Adaptive Test for Problematic Mobile Phone Use - Liu, Xiaorui; Lu, Hui; Zhou, Zhao; Chao, Miao; Liu, Tour (Frontiers in Psychology, 2022)
The great number of mobile phone users in the world has increased in recent years. More time spent on a phone, more negative effects such as problematic mobile phone use. Many researchers have devoted themselves to revise tools to measure problematic mobile phone use better and more precisely. Previous studies have shown that these tools have good reliability and validity, but that most of them have some shortcomings because they were traditional paper-and-pencil tests based on Classical Test Theory (CTT). This study, based on Item Response Theory (IRT) in order to solve these shortcomings, developed Computerized Adaptive Test for problematic mobile phone use (CAT-PMPU) and discussed the performance of CAT-PMPU. Then, we used real data to simulate CAT, and the measurement accuracy and reliability between a paper-and-pencil test and CAT-PMPU were compared under the same test length. The results showed that CAT-PMPU was better than the paper-and-pencil test in all aspects, and that it can reduce the number of items and improve measurement efficiency effectively. In conclusion, the CAT-PMPU was developed in this study has good reliability, and it provided novel technical support for the measurement of problematic mobile phone use. It had a good application prospect.